ANALISA DAYA DUKUNG TIANG PANCANG STATIS DAN DINAMIS PADA BENDUNGAN GERAK SEMBAYAT GRESIK - Reno Dwi Santoso; Dwi Kartikasari (Litbang Pemas - Universitas Islam Lamongan, 2017)
In general, foundation is defined as the underground building that continues the load from the weight of the building itself and fromthe external load that works at the buildi ng to the ground around it. Carrying capacity analysis of pile is needed to get the planning of foundation that meetsthe requirements. There are many calculation methods used to analyze the carrying capacity of the pile, but it needs to consider which method is more fulfilling from the data in the field, for that, it needs carrying capacity analysis of several methods based on field data using sondir data and compared to one another to obtain more realistic results. Capacity analysis method of pile on the construction of Dams Motion in Sembayat Gresik uses static and dynamic methods. In the dynamic method, it use several methods, those are Hiley equation, Wika Method, ENR method, Eytelwein Method, Navy-Mc.Kay Method, and Michigan State Highway of Commission Method. While in the static method, it uses Luciano Dacourt Method. From the analysis of the static pile carrying capacity obtained the result that pile carrying capacity calculation of Luciano Dacourt Method is smaller, pull Q permitted 15.25 tons and maximum press Q permitted 41.55 tons compared with the calculation method by using kalendering result of Eytelwein Method. In Eytelwein Method, the minimum pile carrying capacity is 61.566 tons of calculations in GW 1.